Powiedziane i przemilczane. Rzecz o katolicyzmie Ignacego Krasickiego na podstawie jego twórczości literackiej - Magryś, Roman (Tematy i Konteksty, 2016)
The article presents Ignacy Krasicki’s religiousness in the light of anthropology, which assumes that the man can, at the same time, show different attitudes concerning his outlook, resulting from being affected by simultaneous contradictory cultural paradigms. The author reveals the symptoms of secular thinking on the foundations of human morality in literary texts by the Bishop of Warmia, accompanied by religious traditionalism in the same or different literary works. The goal of the article is to provoke discussion on the personality of people in the Age of Enlightenment, which may not be explicit, but can be composed of heterogenous cultural elements.